Inovasi Pengembangan Stunting Early Detection Spinner (SEDPIN) terhadap Keterampilan Mahasiswa dalam Menentukan Status Pertumbuhan pada Anak Dibawah 5 Tahun - Isra Nur Utari Syachnara Potabuga; Elzina Dina De Fretes; Yosina Atanai; Meriam Christiani Hukubun (Universitas Malahayati Lampung, 2026)
ABSTRACT Stunting is a global health problem that has a serious impact on the quality of children’s growth and development. Early detection of growth status is an essential step in preventing stunting; however, the skills of nursing students in assessing child growth need to be improved. This study aims to develop and examine the effectiveness of the Stunting Early Detection Spinner (SEDPIN) innovation in enhancing students’ skills in determining growth status among children under five years old. The study employed a pre-experimental one-group pretest–posttest design involving a sample of 60 nursing students from the Fakfak Nursing Study Program. Research instruments included a skills observation sheet and a performance assessment checklist. Data analysis was conducted using a paired t-test. The results showed a significant improvement in students’ skills after the intervention, with the mean pretest score of 60 increasing to 90 in the posttest (p 0.05). SEDPIN was considered easy to use, practical, and effective as a clinical learning media. In conclusion, the SEDPIN innovation is effective in improving students’ skills in early detection of growth status among children under five and is recommended for implementation in pediatric nursing practicum learning. Keywords: Stunting, Early Detection, SEDPIN, Anthropometry, Nursing Students ABSTRAK Stunting merupakan masalah kesehatan global yang berdampak serius terhadap kualitas tumbuh kembang anak. Deteksi dini status pertumbuhan merupakan langkah penting untuk mencegah stunting, namun keterampilan mahasiswa keperawatan dalam melakukan penilaian pertumbuhan anak harus di tingkatkan. Penelitian ini bertujuan untuk mengembangkan dan menguji efektivitas inovasi Stunting Early Detection Spinner (SEDPIN) dalam meningkatkan keterampilan mahasiswa dalam menentukan status pertumbuhan anak di bawah lima tahun. Desain penelitian menggunakan pre-experimental one group pretest-posttest dengan sampel 60 mahasiswa tingkat Program Studi Keperawatan Fakfak. Instrumen penelitian berupa lembar observasi keterampilan dan checklist penilaian performa. Analisis data menggunakan paired t-test. Hasil penelitian menunjukkan peningkatan signifikan keterampilan mahasiswa setelah intervensi, dengan rata-rata nilai pretest 60 meningkat menjadi 90 pada posttest (p 0,05).SEDPIN dinilai mudah digunakan, praktis, dan efektif sebagai media pembelajaran klinik. Kesimpulannya, inovasi SEDPIN efektif meningkatkan keterampilan mahasiswa dalam deteksi dini status pertumbuhan anak balita dan direkomendasikan untuk digunakan dalam pembelajaran praktikum keperawatan anak. Kata Kunci: Stunting, Deteksi Dini, SEDPIN, Antropometri, Mahasiswa Keperawatan.